RELATIONSHIPS BETWEEN SHORT-TERM BLOOD PRESSURE VARIABILITY AND LEFT VENTRICULAR DIASTOLIC DYSFUNCTION IN HYPERTENSIVE PATIENTS. (April 2021) - Mulé, Giuseppe; Guarino, Laura; Nardi, Emilio; Calandra, Leonardo; Di Maggio, Antonio; Sorce, Alessandra; Mancia, Ettore; Giambrone, Marta; Imbrogio, Vincenzo; Cottone, Santina
Abstract : Objective: Although an accurate assessment of fast blood pressure (BP) fluctuations occurring within the 24 hours, ideally requires continuous beat-to-beat recording, its assessment is also possible through non-invasive, intermittent 24 h ambulatory BP monitoring (ABPM) Short-term BP variability (SBPV) seems to be relevant to the pathophysiology of target organ damage and to the incidence of clinical events. Our study was aimed to assess in hypertensive patients the relationships between some echocardiographic indices of DD and SBPV. Design and method: We enrolled 289 hypertensive subjects (age: 54 ± 16 years) recruited from those consecutively attending our Hypertension Centre. All the patients underwent: a 24-h ambulatory BP monitoring (ABPM) and an echocardiogram. We calculated the following indices of SBPV: standard deviation and average real variability (ARV) of diurnal and nocturnal systolic (SBP) and diastolic BP (DBP), 24 h weighted SD and ARV of SBP and DBP. Diastolic function was assessed by measuring from the mitral inflow profile, the E-wave (E) and A-wave (A) peak velocities, E/A ratio and E-deceleration time. Isovolumic relaxation time was calculated between aortic valve closure and the start of E-wave. Tissue Doppler imaging of the mitral annulus was obtained placing the sample volume in the lateral mitral valve annulus to evaluate: systolic peak velocity (Sm), early (Em) and late (Am) diastolic myocardial velocities. The E/em ratio was also calculated. Results: All the indices of systolic SBPV examined showed significant correlations with A-wave and with Em (p < 0.01). The correlations with the greatest strenght were those between Em and ARV of 24 h SBP (r = -0.273; p < 0.001) and between Em and weighted SD of 24 h SBP (r = -0.307; p < 0.001). These associations held even after adjustment in multiple regression models for confounders such as age, sex, average 24 h systolic BP and heart rate (p < 0.01). Conclusions: Our findings, showing an independent association between SBPV and some indices of diastolic dysfunction able to predict the development of heart failure, corroborate the concept that an increased short-term systolic BP variability may not be an innocuous phenomenon.